Emphasise the role of kangaroo mother care in stabilisation of vitals and weight gain pattern in low birth weight babies inside neonatal intensive care unit - Bhatt, Shwetal M.; Mehta, Khushboo N.; Maheshwari, Ankita; Parmar, Priyanka C. (International Journal of Contemporary Pediatrics, 2021)
Background: Kangaroo mother care (KMC) is routinely practiced in post-natal wards for care of stable low birth weight (LBW) infants. Objectives of the study were conducted to emphasize on the role of KMC in vitals stabilization and weight gain in LBW babies inside neonatal intensive care unit (NICU). Methods: Cross-sectional analytical quantitative study. Results: A total of 80 babies (48 males and 32 females) were enrolled and given KMC inside NICU. Mean birth weight was 1330 grams. Mean gestational age was 33 weeks (range 30-38 weeks). KMC was initiated within 72 hours of life in majority of babies (71%). Though 65% of them required oxygen support via prongs, KMC was started in them, with monitoring of vitals. No episode of apnea was observed during KMC sessions. Mean duration of KMC was 6 days (3-14 days). Heart rate dropped by 3-4 beats per minute (150+2.12 to 146+1.63, Respiratory rate decreased from 53+3.9 to 49+2.7, Oxygen saturation improved by 2-3% (93+0.42 to 96+0.71). Temperature rose from 36.78+0.01 to 37.07+0.02. P value for all vitals was 0.0001, which is considered significant (<0.05). Average weight gain was 76 grams during the average 6 days of KMC inside NICU, (p value=0.0001). Conclusions: KMC was found to be effective for stabilization of vitals in NICU, early initiation and upgradation of feeding, early achievement of weight gain pattern, and early shift to postnatal ward by mother’s side. Also, no adverse effects were noted on the babies.